Layers of exposure risk management measures for the prevention and control of infections of healthcare workers treating COVID-19 patients - Neştian Ștefan Andrei; Turnea Elena-Sabina; Tiţă Silviu-Mihail; Vodă Ana-Iolanda; Poroch Vladimir (PLoS ONE, 2025)
Background COVID-19 has changed the way hospitals manage infections and how healthcare workers (HCWs) carry out their activities. The pandemic has taught us how safety, hygiene and work schedules should be implemented. After the pandemic, a substantial body of research has examined the managerial capacities of health systems, national prevention programmes, and crisis-response strategies. Objective The aim of this study is to determine the most critical risk management measures in the context of COVID-19 pandemic, with a focus both prevention and post-factum control measures. Methodology We conducted a study using a questionnaire previously validated by the World Health Organization, adapted to identify the key organisational measures for preventing and controlling infections during interactions with patients infected with COVID-19 virus. The setting for the study was the “Sf. Ioan cel Nou” County Emergency Hospital, Suceava, Romania. A total of 312 responses were collected between 10.10.2020 and 19.03.2021. The study complied with two ethical protocols, data were analysed using 21.0 version of the Statistical Package for the Social Sciences software. Results Statistical analysis identified four constructs grouping the measures – technical, organisational, human resources, and others, all aimed at preventing the spread of SARS-CoV-2 within and beyond the hospital. In our vision, these four main resulted constructs could be conceptualised similarly to a security system, which aims protects an “asset” from a threat by applying several layers that gradually reduce risk to near zero. Specifically, the first layer involves managing exposure risk by separating contaminated from uncontaminated areas; the second comprises general preventive measures for healthcare workers operating in contaminated areas; the third layer addresses staff attendance and workplace organisation, and the fourth focuses on risks perceived and manifested at the individual level. Conclusion Exposure risk assessment and management follow a logic similar to that of a security system designed to protect an “asset” from a threat. In our case, the health of the HCWs was at risk due to their interactions with COVID-19 patients at “Sf. Ioan cel Nou” County Emergency Hospital, Suceava, Romania. Hypothesis testing indicated that all implemented measures contributed significantly to pandemic management, although a functional exposure risk management system requires effective risk reduction across all 4 layers. Given the validity of the second hypothesis – that preventive measures were generally applied at the hospital – we can conclude that HCWs and managers may primarily focus on this type of preventive measure, mainly addressing the second layer alone. This imbalance risks diverting managerial attention and resources toward the second layer at the expense of the other three.